INVESTIGATING LETHAL EFFECT OF DIFFERENT BOTANICALS AGAINST OXYCARENUS LAETUS KIRBY UNDER LABORATORY CONDITIONS - MIRZA ABDUL QAYYUM, MUHAMMAD ASAD SALEEM, JAVARIA NAZIR (International Multidisciplinary Research Journal, 2018)
For last few years, dusky cotton bug, Oxycarenus laetus (Hemiptera: Lygaeidae) has become an emerging pest of cotton crop threatening cotton production in Pakistan. Onset of insecticidal resistance demands the use the alternate approaches for the control of O. laetus. Plant-based botanicals have the potential to suppress O. laetus at different concentrations. The findings of present study showed that highest mortality (53.13%, 70.83% and 96.91%) of O. leatus was recorded at 1.5%, 2.5% and 5% concentrations after 72h of treatment with N. tabacum. However, O. sanctum harbored lowest mortality (38.10%, 37.50% and 52.91%) at all tested concentrations. Consequently, Nicotiana tabacum was proved as exhibiting competent insecticidal properties for the control of O. laetus.